Every day we live is the future : surviving in a city of disasters - Haynes, Douglas (University of Texas Press, 2017)
"When she was only nine, Dayani Baldelomar left her Nicaraguan village with nothing more than a change of clothes. She was among tens of thousands of rural migrants to Managua in the 1980s and 1990s. After years of homelessness, Dayani landed in a shantytown called The Widows, squeezed between a drainage ditch and putrid Lake Managua. Her neighbor, Yadira Castell?n, also migrated from the mountains. Driven by hope for a better future for their children, Dayani, Yadira, and their husbands invent jobs in Managua's spreading markets and dumps, joining the planet's burgeoning informal economy. But a swelling tide of family crises and environmental calamities threaten to break their toehold in the city. Dayani's and Yadira's struggles reveal one of the world's biggest challenges: by 2050, almost one-third of all people will likely live in slums without basic services, vulnerable to disasters caused by the convergence of climate change and breakneck urbanization. To tell their stories, Douglas Haynes followed Dayani's and Yadira's families for five years, learning firsthand how their lives in the city are a tightrope walk between new opportunities and chronic insecurity. Every Day We Live Is the Future is a gripping, unforgettable account of two women's herculean efforts to persevere and educate their children. It sounds a powerful call for understanding the growing risks to new urbanites, how to help them prosper, and why their lives matter for us all"--Jacket